ASSESSING THE IMPACT OF CHANGE MANAGEMENT STRATEGIES ON THE ADMINISTRATION OF KENYA PRISONS SERVICE - Kiplangat, Bii John; Shisia, Adam; Kiilu, Redempta M. (Semantic Scholar, 2015)
The study sought to understand the Impact of Change Management strategies based on Organizational Culture, Power and Politics and Managerial behavior at the Kenya Prisons Service. Using a descriptive study approach, a sample of 300 respondents were identified using purposive sampling from the four prisons in Nairobi County. The key findings were that gender insensitivity was noted as more male officers were hired in the institutions than female officers. Most officers had low levels of education. The main finding is that the impact of change on the aspects tested was generally low. The research concluded that changes initiated in the Correctional institutions Administration have not been effective since there are low impacts based on aspects of Organizational culture, Managerial behavior and Power and politics at the Kenya Prisons service. The study recommends that Change management implementation strategies need to be properly and adequately managed to successfully reap the benefits of change in a Public Sector setting in terms of Organizational culture, Organizational Power and Politics and Managerial behavior.